(untitled) (Ibrahim Cardiac Medical Journal, 2018)
Objective: This prospective study was carried out to see the effect of engagement of foetal head at term in primigravidae women. Materials and Methods: The study was conducted in the Department of Obstetrics & Gynaecology, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka from June, 2006 to December, 2006. The study included 1440 women who were admitted in the hospital during the above mentioned period. All women were examined to see the engagement of foetal head by the rule of 5 at or after 38 weeks pregnancy. Of them, 262(18.2%) presented with engagement of foetal head and 1178(81.8%) without foetal head engagement. Main outcome measure was the effect of engagement of foetal head at term in primigravidae women. Foeto-maternal outcomes were recorded by clinical observation. Result: No significant differences were found in terms of demographic and anthropometric characteristics (like age, height and weight) between primigravidaewomen who had engaged foetal head and women who did not have foetal head engaged (p = 0.969; p = 0.258 and p = 0.139). Three-quarters (74.96%) of the patients at presentation were in labour and the rest were not in labour. Duration of labour was significantly higher in non-engaged group compared to those who had foetal head engaged.The incidence of non-engagement of foetal head in nulliparous women at or after 38 weeks of pregnancy was 81.8%; but only 11.5% of them had cephalo-pelvic disproportion (CPD). The incidence of vaginal delivery in the non-engaged and engaged group was 36.9% and 66.1% respectively. Most of the patients underwent caesarean section due to foetal distress and indications other than CPD. Conclusion: The findings of the study suggest that the obstetricians should take a conservative attitude and a non-engaged foetal head at term in a primigravid woman should not by itself be an indication for caesarean section. Ibrahim Card Med J 2016; 6 (1&2): 62-66